Burial practices in southwest Britain and northwest France (c.600-1050AD): a comparative analysis - Troadec, Solenn (2020)
British and French archaeology have both dedicated a central place to the study of the nature and impact of connections linking the Continent to the British Isles in the early medieval period. Research is, however, still limited in the western Channel, great migration and conversion period theories remaining the traditional explanation for cultural parallels between facing regions. This thesis constitutes the first detailed multiscale comparative analysis of burial practices in southwest Britain (Cornwall, Devon, Dorset, Somerset and Hampshire) and northwest France (Brittany, Loire Atlantique and Normandy) for the period c.600-1050AD, exploring the changes and permanencies in funerary rites in a period of great social, economic and religious transformation, and offering a new understanding of the connections existing in the western Channel throughout the early Middle Ages. The scale and nature of this project required the creation of a new comparative methodology relying on a precise bi-lingual vocabulary, allowing for the collection and analysis of data gathered in countries of distinctive archaeological traditions. Various aspects of the burial practice are considered through a thematic analysis, facilitating the presentation and study of data at different levels of precision, highlighting individual peculiarities and communal traditions alongside wider regional and Cross-Channel trend. This new approach reveals the diversity of funerary practices coexisting at different scales, offering a new perspective on the expression of multiple layers of identity, each funerary choice resulting from a composite sum of influences and personal experiences. Additionally, this study challenges previous hypothesis born from migration period theories and provides a re-assessment of the impact of the conversion period on the relationship between the dead and the living. Finally, this project emphasises the need for more comparative analyses, borrowing from different archaeological traditions to offer a new perspective on the study of burial practices in facing regions of the Channel and unlocking the potential of further European collaborations.